DROPLET IMPACT BEHAVIOUR OF MODIFIED BIOPOLYMER ON UREA SURFACE: EFFECT OF FILLERS - SAMSUDIN, YON NORASYIKIN (2016)
Biopolymer coating material is favoured as the coated material because it can degrade and is harmless to the environment. The polymer matrix of tapioca starchurea- borate (SUB) has been known to have the potential as a controlled release formulation. Three types of fillers which are lignin (SUB-Li), nanoclay bentonite (SMMT) and nanoclay halloysite (S-HNT) were reinforced into the SUB matrix to improve the wettability and mechanical properties. In the urea coating process, the wetting stage plays an important phase where the material spreads on urea surface to form a thin film layer which determines the coating uniformity of coated urea. The droplet impact behaviour will provide further info on the solid-liquid interaction of modified biopolymer on the urea surface. Thus, the objective of this study is to identify which modified biopolymer composition has good droplet impact behaviour when impacting on the urea surface at optimum temperature. The droplet impact studies was analysed with three responses which are dynamic contact angle, spreading factor and penetration rate by using image analysis.